Solusi Dan Kontributif Sistem Lingkungan Arsitektur Terhadap Permasalahan Pembangunan IKN Di Kalimantan Timur - Ikhsan Mahran Hakim (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Since the Government declared the New Capital City (IKN) on August 26, 2019, a number of studies have been published discussing the goals, challenges, hopes, and impacts of moving the IKN from Jakarta to East Kalimantan. The IKN was set in East Kalimantan because the logistics industry in the province is very developed. One example of Biotanya, in East Kalimantan is the native species that allow life to survive in remote areas. In addition, the population of East Kalimantan, the majority of whom are Javanese, are accustomed to accepting foreigners and assimilating their culture. (Yanita Petriella - Bisnis.com). The reasons for moving the IKN are inseparable from the various problems that arise next and the most prominent discussed further is regarding the development problems of the IKN.